Workfunction variation across surface of an H-terminated diamond film measured using Kelvin probe force microscopy - Lay, J.; O'Donnell, Kane; May, P. (Elsevier BV, 2011)
With the ability to image both topography and contact potential difference simultaneously, Kelvin probe force microscopy (KPM) is an effective tool for the electrical characterisation of diamond surfaces. In this work we measure variations in contact potential difference across the surfaces of boron-doped diamond films in order to investigate work function variations caused by surface features. Significantly, we demonstrate work function variations in excess of 300 mV across the surfaces of two differently prepared diamond films. Variations of this magnitude may have implications for the use of diamond in a number of electronic applications.